Estimation of Lifetime and Reliability of Input Rectifier in Variable Frequency Drives. Issue 1 (September 2020) - Ramesh, P; Govarthanan, R; Palanisamy, K; Paramasivam, S
Abstract: This research paper investigates the causes of power module failures in front-end rectifier of variable frequency drive (VFD) and their lifetime estimation. The front-end rectifier plays an important role in the electrical system for energy conversion. However, from the industrial survey it is found that they are sensitive to harsh operating conditions and are prone to damage. Hence, it becomes inevitable to analyse the causes of their failure and lifetime. Due to prolonged usage, sudden variations in supply and load, the power modules will be subjected to stresses such as overvoltage, voltage variations due to sag, phase unbalance, over current, temperature, harmonics and pre-distortions. The major causes of failure are due to several stresses such as solder joint break, bond wire lift-off, cracks in power modules are discussed. In this paper, the lifetime of the power module is estimated for a given mission profile data. The junction temperature profile is obtained from the VFD Front-end rectifier simulation model. The number of temperature cycles from the temperature profile is estimated using cycle counting methods. Lifetime estimation and damage modelling is done using Coffin-Manson rule and Palmgren Miner rules. All these modelling and simulations are done for a specific VFD power size using MATLAB and PLECS.